Various Soil Types, Organic Fertilizers and Doses with Growth and Yields of Stevia rebaudiana Bertoni M - Dian Pratama Putra Saragih; Azwar Ma'as; Soepriyanto Notohadisuwarno (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Stevia has several advantages including the level of sweetness that reaches 100-200 the sweetness of sugar cane and low calorie so that it is safe to be consumed by diabetics and obesity. The possibilities of plants to grow on soil properties and fertility become an important issue in agricultural cultivation systems and with the treatment of organic fertilizers will produce significant results in agricultural research. The experiments were arranged in Completely Randomized Design (CRD) with 3 various soil types of treatment factors: Alfisol (Al), Andisol (An) and Vertisol (Ve) soil with 2 types of organic fertilizer ie Compost (K) and Manure (SK) and 3 kinds of doses 20 ton/ha (12 g/pot), 40 ton/ha (24 g/pot) and 60 ton/ha (36 g/pot). Observational data were analyzed using variance analysis (ANOVA), if there was a real significant difference, the Duncan 5% real level to know the comparison between treatments. The results showed that the soil type of Vertisol given by compost fertilizer at 40 ton/ha (24 g/pot) gave the highest yield on all agronomic parameters, i.e. number of leaves, number of clumps, plant length, dry weight and wet weight. The result of production analysis shows that stevia at lowland can yield higher, on vertisol 2,7 ton/ha, alfisol 1 ton/ha and andisol 0,4 ton/ha whereas in highland that yield only 0,3 ton / ha (standard fertilizers) but with increasing amounts of biomass of stevia leaves can increase stevioside levels significantly.